2021
DOI: 10.3390/act10020030
|View full text |Cite
|
Sign up to set email alerts
|

Sensuator: A Hybrid Sensor–Actuator Approach to Soft Robotic Proprioception Using Recurrent Neural Networks

Abstract: Soft robotic actuators are now being used in practical applications; however, they are often limited to open-loop control that relies on the inherent compliance of the actuator. Achieving human-like manipulation and grasping with soft robotic actuators requires at least some form of sensing, which often comes at the cost of complex fabrication and purposefully built sensor structures. In this paper, we utilize the actuating fluid itself as a sensing medium to achieve high-fidelity proprioception in a soft actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Experiments showed that this method is feasible for realizing proprioception and is robust to common sensor failures. 262 There is similar research using soft robotic skin to contact the outside and the collected signals are combined with RNN for analysis. Truby et al used deep learning to build a framework for predicting the 3D configuration of a soft robot from the feedback of soft and proprioceptive sensor skin.…”
Section: Stimuli-response Materials (Srms)mentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments showed that this method is feasible for realizing proprioception and is robust to common sensor failures. 262 There is similar research using soft robotic skin to contact the outside and the collected signals are combined with RNN for analysis. Truby et al used deep learning to build a framework for predicting the 3D configuration of a soft robot from the feedback of soft and proprioceptive sensor skin.…”
Section: Stimuli-response Materials (Srms)mentioning
confidence: 99%
“…Experiments showed that this method is feasible for realizing proprioception and is robust to common sensor failures. 262…”
Section: Applicationsmentioning
confidence: 99%
“…Thuruthel et al embedded soft sensors into the actuator to obtain bending data and used it to train an RNN that can predict the position of the actuator's tip and the force applied by it [17]. Another group used a Bidirectional Long Short-Term Memory (BiLSTM) network, a type of RNN, to estimate the position of a hydraulic soft hybrid sensor-actuator [18].…”
Section: Related Workmentioning
confidence: 99%
“…Xie et al [9,10] proposed a 3D-printed pipe-climbing robot actuated by the flat modular pneumatic artificial muscle consisting of thin-film cylinder modules. Preechayasomboon et al [11] presented a hybrid bellows-style sensor-actuator with salt water inside. Gravagne et al [12] studied a class of cable-driven robot manipulators termed continuum robots such as the Clemson tentacle manipulator, consisting of two independent sections on a continuous backbone with a thin elastic rod.…”
Section: Introductionmentioning
confidence: 99%